The Plastic treaty: What is in it for Africa? - Deborah Oluwaseun Shomuyiwa; Francisca Ogochukwu Onukansi; Maria Ivanova; Don Eliseo Lucero‐Prisno III (Wiley, 2023)
Abstract The new plastic treaty, slated for 2024, represents a shift in the global fight to address environmental pollution and degradation. The international agreement, unlike previous resolutions, covers the lifecycle of plastics and represents a legally binding instrument for ending plastic pollution across all ecosystems. Plastic waste contamination poses significant challenges to African nations. It challenges food security, ecological variation and economic development. The African region has been identified with a high level of enactment of waste management policies but a deficiency of sustainable measures to adopt and implement these policies. The new treaty could provide an instrument for collaboration and innovation and set the stage for Africa to transition to a sustainable plastics environment that promotes zero‐waste.